MENINGKATKAN HASIL BELAJAR MELALUI PEMBELAJARAN KOOPERATIF TIPE TEAMS GAME TOURNAMENT (TGT) DIKOMBINASIKAN DENGAN TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) PADA MATA PELAJARAN DASAR-DASAR MANAJEMEN KELAS X SMK KARYA EKOPIN DI JAKARTA TIMUR - Widya Parimita; Umi Widyastuti; Monica Nining Lestari (Jurnal Ilmiah Econosains, 2012)
Abstract This study aims to increase student’s learning results through implementation of cooperative learning model based on type of Teams Game Tournament (TGT) combining with Student Teams Achievement Divisions (STAD) in management foundamental subject. The action research was conducted with three cycle. Each ycle is formulated with four stages: planning, action, observation and reflections. This research shown that the implementation of cooperative learning model based on type of Teams Game Tournament (TGT combined with Student Teams Achievement Divisions (STAD) have positive contributiom in increasing student’s learning achievement.